The Effect of Principal Supervision on Teacher Performance at SDN Wonosari, Pasuruan - Handayani, Puji; Thohirin, Ahmad; Suyitno (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe the implementation of principal supervision and its contribution to teacher performance at SDN Wonosari, Pasuruan Regency. The research employed a qualitative approach with a descriptive design. The research subjects consisted of the principal and teachers selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings indicate that principal supervision was implemented through planning, implementation, and follow-up processes that were flexible and oriented toward teacher professional development. Communicative and continuous supervision contributed to improving teacher performance, particularly in lesson planning, classroom instruction, and work motivation. This study provides a contextual understanding of the role of principal supervision in enhancing teacher performance at the elementary school level.